Evaluating the influencing factors high order thinking skills of outstanding student by analytic hierarchy process (AHP) method - Dame Ifa Sihombing; Tutiarny Naibaho; Adi Suarman Situmorang (AXIOM : Jurnal Pendidikan dan Matematika, 2024)
This study aims to identify various factors that influence the development of higher-order thinking skills in the Master's program mathematics education department at Universitas HKBP Nommensen. The systematic AHP method allows for accurate weighting and prioritization of various factors influencing HOTS. These results provide a strong foundation for policy recommendations and educational practices aimed at enhancing higher-order thinking skills among outstanding students. The ranking results of the factors influencing HOTS among 100 outstanding students in the Master's program in Mathematics Education were analyzed using the hierarchy of one factor over another. By observing the three criteria and ten sub-criteria, it can be concluded that Criterion 2, or students, is the most influential factor in determining students' HOTS with a weight of 0.53. The second influencing factor is Criterion 1, or lecturers, with a weight of 0.13, and the least influential factor is the learning environment with a weight of 0.07. Matrix interpretation shows that the Lecturer factor (K1) is considered more important than the Student factor (K2) and the Learning Environment factor (K3) in influencing the HOTS of high-achieving students. This highlights how important lecturers are in helping students develop higher-order thinking abilities.